Historical blocking: CN 2020-04-23 (China) - Voidly (Voidly Global Censorship Index, 2020)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2020-0002. Severity: critical. Confidence: 97%